Role of Learning Accountancy in Increase Literacy Finance Vocational High School Students - Aliah, Nur; Rizkina, Miftha; Harianty, Savanda (PT Aksara Indo Rajawali, 2024)
This study aims to identify role learning accountancy in increasing literacy finance vocational high school students majoring in accounting at SMK Negeri 1 Medan. Literacy finance become an essential skill for the young generation to manage finances personally, especially in the middle of the modern economy and the development of technology. Learning accounting in vocational schools is designed to give knowledge and theoretical and practical skills in management finance, which is expected to form attitudes and behaviours of positive finances. Research This uses a descriptive qualitative approach, with semi-structured interviews of 16 students majoring in accounting. Focus interview covers aspects of curriculum, learning methods, practice learning, use of technology accounting, and evaluation learning. Research results show that learning accountancy contributes significantly to the literacy of finance students, particularly in aspects of knowledge finance, skills management finance, attitude to finance, and behaviour finance every day. However, it was found that there is a need for multiple practices based on the case, improved use of technology accounting, and strengthened evaluation based on the project. Research This concludes that learning accounting in vocational schools can become an effective means of increasing the literacy of finance students. However, several aspects of the curriculum and learning methods still need repair for more optimal results.